2017
DOI: 10.1177/1747493017730745
|View full text |Cite
|
Sign up to set email alerts
|

Fibrinolytic for treatment of intraventricular hemorrhage: A meta-analysis and systematic review

Abstract: Background Intraventricular hemorrhage is a significant cause of mortality and morbidity worldwide. Treating intraventricular hemorrhage with intraventricular fibrinolytic therapy via a catheter is becoming an increasingly utilized intervention. Aims This meta-analysis aimed to investigate the role of intraventricular fibrinolytic treatment in hypertensive intraventricular hemorrhage patients and evaluate the effect sizes for survival as well as level of function at differing time points. Summary of review Pub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 30 publications
2
16
0
3
Order By: Relevance
“…However, in a sensitivity analysis, correction for publication bias estimated an increased risk of intracranial bleeding and a lower risk of ventriculitis for patients receiving IVF. Previous systematic reviews have been cautiously optimistic regarding the use of IVF in IVH [16,17,40]. Recently, a systematic review from Wang et al [16] concluded that IVF was associated with lower risk of mortality (RR 0.63, 95% CI 0.47-0.83) and ventriculitis (RR 0.57, 95% CI 0.35-0.93), but did not change the likelihood of poor functional outcome (RR 0.96, 95% CI 0.83-1.11), shunt dependence (RR 1.06, 95% CI 0.75-1.49), or rehemorrhage (RR 0.57, 95% CI 0.35-0.93).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in a sensitivity analysis, correction for publication bias estimated an increased risk of intracranial bleeding and a lower risk of ventriculitis for patients receiving IVF. Previous systematic reviews have been cautiously optimistic regarding the use of IVF in IVH [16,17,40]. Recently, a systematic review from Wang et al [16] concluded that IVF was associated with lower risk of mortality (RR 0.63, 95% CI 0.47-0.83) and ventriculitis (RR 0.57, 95% CI 0.35-0.93), but did not change the likelihood of poor functional outcome (RR 0.96, 95% CI 0.83-1.11), shunt dependence (RR 1.06, 95% CI 0.75-1.49), or rehemorrhage (RR 0.57, 95% CI 0.35-0.93).…”
Section: Discussionmentioning
confidence: 99%
“…The American Heart Association/American Stroke Association guidelines conclude that the efficacy and safety of fibrinolytics in IVH are uncertain [15]. Recently, the CLEAR-III study [14] evaluated the effect of IVF for IVH resulting from small IPHs and observed a decreased risk of mortality, which was endorsed by previous meta-analyses [16,17], while no improvement of good functional outcome (GFO) (modified Rankin Score [mRS] equal to or lower than 3) was observed [14]. Previous systematic reviews have reached different conclusions regarding functional outcome, and discussions regarding the safety of (repeated) injections of fibrinolytic agents into fresh hemorrhages are ongoing [16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…Podemos dividir a hemorragia intraventricular em dois tipos: primárias e secundárias. Enquanto o primeiro possui uma maior expectativa de sobrevivência com menores taxas de complicações, HIV secundária a hipertensão arterial sistêmica, doença de Moyamoya, má formação arteriovenosa, aneurisma intracerebral, entre outras, são majoritariamente severas com altas taxas de morbimortalidade 2,4 .…”
Section: Discussionunclassified
“…Um trabalho americano comparou a aplicação de 3mg de Alteplase vs placebo, a cada 12h, até a resolução do coágulo, também com bons desfechos 10 . Outros trabalhos e revisões demonstraram doses e formas diferentes de aplicação, todos com resultados semelhantes 1,2,5,6 .…”
Section: Discussionunclassified
See 1 more Smart Citation